Interteaching and Lecture: A Comparison of Long-Term Recognition Memory. (October 2014) - Saville, Bryan K.; Bureau, Alex; Eckenrode, Claire; Fullerton, Alison; Herbert, Reanna; Maley, Michelle; Porter, Allen; Zombakis, Julie
Although a number of studies suggest that interteaching is an effective alternative to traditional teaching methods, no studies have systematically examined whether interteaching improves long-term memory. In this study, we assigned students to different teaching conditions—interteaching, lecture, or control—and then gave them a multiple-choice quiz immediately after exposure to the material and again after 1 week and 1 month. We found that students in the interteaching condition had significantly higher quiz scores than students in the lecture and control conditions after every session. Although additional research is necessary to determine whether our findings generalize to classroom settings and to different testing formats, these results suggest that interteaching may enhance long-term recognition memory better than lecture-based teaching methods.